REVIEW PAPERThe cardiologists\' dream may come true – vascular therapy - Rusiecka, Ewa; Banach, Maciej (Archives of Medical Science, 2005)
Recently there has been a great evolution of new diagnostic and therapeutic methods of cardiovascular diseases. However, they still remain the most common death cause in the Western countries. Despite the fact that new methods of dealing with cardiovascular diseases like for example percutaneous coronary interventions or coronary artery bypass grafting are constantly being improved, there is still a group of patients that can not undergo the routine treatment. It is a good stimulus for searching different ways of dealing with cardiovascular diseases. New vascular methods based on interfering in processes of vessels\' creation and regression, seem to be an interesting direction of current studies. This article reviews the basis of vasculogenesis, angiogenesis and arteriogenesis and angiogenic therapies, learned from the latest trials. Vascular therapies offer a promise as a novel treatment for ischemic heart disease, particularly for patients who are not candidates for current methods of revascularization.